Proceedings of the 2019 Conference on Empirical Methods in Natural Language Processing and the 9th International Joint Conferen 2019
DOI: 10.18653/v1/d19-1002
|View full text |Cite
|
Sign up to set email alerts
|

Attention is not not Explanation

Abstract: Attention mechanisms play a central role in NLP systems, especially within recurrent neural network (RNN) models. Recently, there has been increasing interest in whether or not the intermediate representations offered by these modules may be used to explain the reasoning for a model's prediction, and consequently reach insights regarding the model's decision-making process. A recent paper claims that 'Attention is not Explanation' (Jain and Wallace, 2019). We challenge many of the assumptions underlying this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
487
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 608 publications
(541 citation statements)
references
References 15 publications
(12 reference statements)
9
487
2
Order By: Relevance
“…The present analysis identifies associations between attention and various properties of proteins. It does not attempt to establish a causal link between attention and model behavior [28,84], nor to explain model predictions [35,87]. While the focus of this paper is reconciling attention patterns with known properties of proteins, one could also leverage attention to discover novel types of properties and processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present analysis identifies associations between attention and various properties of proteins. It does not attempt to establish a causal link between attention and model behavior [28,84], nor to explain model predictions [35,87]. While the focus of this paper is reconciling attention patterns with known properties of proteins, one could also leverage attention to discover novel types of properties and processes.…”
Section: Discussionmentioning
confidence: 99%
“…Interpreting attention on natural language sequences is a well-established area of research [12,30,87,90]. In some cases, it has been shown that attention correlates with syntactic and semantic relationships in natural language [15,32,83].…”
Section: Interpreting Models In Nlpmentioning
confidence: 99%
“…It then becomes hard if not impossible to pinpoint the reasons behind the wrong output of a neural architecture. Interestingly, attention could provide a key to partially interpret and explain neural network behavior [5]- [9], even if it cannot be considered a reliable means of explanation [10], [11]. For instance, the weights computed by attention could point us to relevant information discarded by the neural network or to irrelevant elements of the input source that have been factored in and could explain a surprising output of the neural network.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a debate on whether attention can be used to explain model decisions (Serrano and Smith, 2019;Jain and Wallace, 2019;Wiegreffe and Pinter, 2019), we thus present additional analysis of our proposed method based on saliency maps (Ding et al, 2019). Saliency maps have been shown to better capture word alignment than attention probabilities in neural machine translation.…”
Section: Discussionmentioning
confidence: 99%